2011
DOI: 10.1002/jmv.22243
|View full text |Cite
|
Sign up to set email alerts
|

Enteric viruses in healthy children in cameroon: Viral load and genotyping of norovirus strains

Abstract: Data regarding prevalence of noroviruses (NoVs) among asymptomatic persons are scarce. The current study carried out on samples from Cameroon describes the asymptomatic shedding of NoVs and other enteric viruses in healthy children and in adults infected with HIV but lacking symptoms of gastroenteritis. Enteric viruses were common with a prevalence of 53.7% in the children, and 35.5% in the adult participants. Multiple enteric viruses (2-5 agents) were detected in fecal samples from 65% of the children, and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
58
3
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 42 publications
15
58
3
2
Order By: Relevance
“…Except for studies in South Africa Murray 2013), Botswana (Mattison et al 2010) and Burkino Faso (Nordgren et al 2013), the occurrence of NoV GI.1 does not appear to be widely reported in Africa as no GI.1 strains were detected in diarrhoeal stool samples from children in Nairobi, Kenya (Mans et al 2014) nor in the clinical specimens (Silva et al 2008;Abugalia et al 2011;Ayukekbong et al 2011;Trainor et al 2013) or sewage samples (Sdiri-Loulizi et al 2010) from other African countries. Norovirus GI.3 however, appears to more prevalent in African regions (Ayukekbong et al 2011;Yassin et al 2012;Trainor et al 2013), including Kenya (Mans et al, 2014). The GI.3 strains identified in this study grouped into four distinct clusters ( Figure 1) and showed 94% -97% nucleotide sequence identity to strains from Russia (GU138161), Japan (AB187514), Sweden (JN603244), Burkina Faso (JX416392), South Korea (HQ213844) and Vietnam (HE716748).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Except for studies in South Africa Murray 2013), Botswana (Mattison et al 2010) and Burkino Faso (Nordgren et al 2013), the occurrence of NoV GI.1 does not appear to be widely reported in Africa as no GI.1 strains were detected in diarrhoeal stool samples from children in Nairobi, Kenya (Mans et al 2014) nor in the clinical specimens (Silva et al 2008;Abugalia et al 2011;Ayukekbong et al 2011;Trainor et al 2013) or sewage samples (Sdiri-Loulizi et al 2010) from other African countries. Norovirus GI.3 however, appears to more prevalent in African regions (Ayukekbong et al 2011;Yassin et al 2012;Trainor et al 2013), including Kenya (Mans et al, 2014). The GI.3 strains identified in this study grouped into four distinct clusters ( Figure 1) and showed 94% -97% nucleotide sequence identity to strains from Russia (GU138161), Japan (AB187514), Sweden (JN603244), Burkina Faso (JX416392), South Korea (HQ213844) and Vietnam (HE716748).…”
Section: Discussionmentioning
confidence: 99%
“…Strains of NoV GII.17 were identified in clinical specimens collected during 1999-2000 from human immunodeficiency virus (HIV)-infected children at a care center in Kenya (Mans et al 2014) suggesting that GII.17 has been in circulating in urban and rural Kenyan communities for a number of years. Nucleotide sequence information on NoV GII.17 strains from Burkina Faso (Nordgren et al 2013), Morocco (KJ162374), Cameroon (Ayukekbong et al 2011) and South Africa (Murray et al 2013) are available in GenBank. Although NoV GII.17 seems to be prevalent in some parts of Africa this genotype was not identified in clinical specimens (Silva et al 2008;Abugalia et al 2011;Hassine-Zaafrane et al 2013;Huynen et al 2013;) and environmental samples (Sdiri-Loulizi et al 2010) from many other African regions and the GII.17 predominance appears to be peculiar to Kenya.…”
Section: Discussionmentioning
confidence: 99%
“…There is no clear animal reservoir for HuNoV, suggesting that it has other adaptations for viral maintenance between outbreaks. Asymptomatic and persistent shedding is likely to be one way that HuNoVs are maintained (4)(5)(6)(7)11), yet many questions remain about the mechanism of NoV persistence. Furthermore, while asymptomatic shedding has been demonstrated for many enteric viruses (43)(44)(45), a tractable model has not been established in which to study enteric persistence.…”
Section: Discussionmentioning
confidence: 99%
“…There is no evidence for an animal reservoir of HuNoV, suggesting that asymptomatic shedding within the human population initiates symptomatic infection. Indeed, PCR-based detection has shown that HuNoVs are present in asymptomatic individuals within a variety of communities and ranges in prevalence from 3 to 13% (4)(5)(6)(7). Furthermore, experimental infection of volunteers revealed that some individuals continue to shed virus for up to weeks after the resolution of symptoms (8), and there are examples where outbreaks likely originated with asymptomatic HuNoV shedders (9)(10)(11).…”
mentioning
confidence: 99%
“…64,65 Long-term shedding was described among children less than 6 months, 63 in elderly, 64 hospitalized and immunosuppressed patients. 62 Predictive modeling of viral shedding classifies shedding into regular shedding with a mean of 14-16 d and long shedding with a mean ranging between 105 and 136 d 66 Recent studies suggest the lack of a significant difference of virus shedding between asymptomatic and symptomatic NoV infections despite the individual variation in virus peak levels detected in stool.…”
Section: Viral Shedding Natural Infection With Nov and Seroprotectionmentioning
confidence: 99%